Terapi Bermain â€œSense Of Pleasure Playâ€ Di Ruang Perawatan Anak RSUD Kota Makassar - Sunarti (Pusat Kajian dan Pengelola Jurnal Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2021)
Hospitalization has various physical and psychological effects. Feelings that often appear in children and parents are anxiety, anger, sadness, fear & feeling. One of the principles of hospitalization in children that must be carried out is to prevent and reduce children's physical and psychological stress which can be done by using relaxation techniques and distraction techniques or distraction from discomfort. Playing activity is one of the distraction techniques performed on children. In principle, the purpose of playing in the hospital is not only to reduce the impact of hospitalization, but also to continue the growth and development phase optimally, develop children's creativity, and be able to adapt more effectively to stress. The partner problems found are the lack of knowledge of patients (children & families) and the awareness of room nurses about the importance of playing therapy in the hospital, the lack of utilization of the available play facilities in the hospital and the lack of awareness of nurses in providing play therapy to children before taking nursing actions. Participants were very enthusiastic, around (80%) participants were actively discussing, most of the participants' knowledge increased by about 85% seen from the activeness of the participants in the question and answer process, participants also understood the importance of providing and utilizing play facilities in the hospital, the children were very enthusiastic and enthusiastic in play, 100% children's cheerfulness.